Ardisia gigantifolia ethanolic extract inhibits cell proliferation and targets cancer stem cells in gastric cancer - Thi Thanh Huong Le; Phu Hung Nguyen; Van Phuong Nguyen; Thy Ngoc Nguyen (Asian Pacific Journal of Tropical Biomedicine, 2023)
Objective: To evaluate the effects of ethanol extract from Ardisia gigantifolia leaves on cell proliferation and cancer stem cell (CSC) number in gastric cancer. Methods: The inhibitory effect of Ardisia gigantifolia extract on the proliferation of MKN45 and MKN74 gastric cancer cells was assessed using 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide assay. Non-adherent culture (3D) model was used to evaluate the effect of the extract on tumorsphere size and number. Moreover, the expression of CD44, ALDH, and p21 was determined by immunofluorescence analysis. Flow cytometric analysis was performed to evaluate cell cycle arrest and the expression of gastric CSC markers CD44 and ALDH. Real-time PCR analysis was also carried out to assess the effect of the extract on the expression of cell cycle-regulated genes. Results: Ardisia gigantifolia extract effectively inhibited cell proliferation with an IC50 of 55.7 µg/mL in MKN45 cells and 123.6 µg/mL in MKN74 cells. The extract also arrested cell cycle in the G0/G1 phase as well as significantly reduced the size and number of tumorspheres. The markedly increased expression of p21 was observed at both mRNA and protein levels in the extract-treated adherent cells and tumorspheres. In addition, Ardisia gigantifolia extract significantly reduced the number of CD44- and/or ALDH-expressing gastric CSC. Conclusions: The development of gastric CSC can be inhibited by the ethanol extract of Ardisia gigantifolia.